A compound operation method of model transformation rule based on OWL. (2018) - Jin, Li; Xuhong, Cheng; Yu, Bai
With the wide application of MDA, many similar or identical business models and software models have subsequently accumulated. The transformation rules for these business models and software models are often similar. Reusing similar transformation rules can improve the efficiency of model transformation. Therefore, it is important to solve the problem of how to use similar constructs and reuse the model transformation rules for improving the precision and efficiency of model transformation. The paper proposes a method based on OWL for the compound operation of model transformation rules. First, the transformation rule space and transformation rules are defined by OWL. Second, the similarity between the business model and software model element is analysed, and the compound operation of the five transformation rules is defined. Finally, to apply the paradigm, a support tool is realised, which can help users implement five compound operations for constructing large granularity model transformation rule.